Castleman’s disease associated with mixed connective tissue disorder and cerebral ischaemia and vasculitis: A rare case and a diagnostic challenge for an infectologist - Popović Dragonjić, Lidija; Jovanović, Maja; Vrbić, Miodrag; Stanojević, Maja; Krstić, Miljan; Tasić, Aleksandar; Živković, Nikola (Vojnosanitetski pregled, 2021)
Introduction. Castleman's disease (CD) or angiofolicullar lymph node hyperplasia is a rare pathologic process characterized by non-neoplastic reactive proliferation of lymphoid tissue. Mimicking clinical and laboratory signs of infection, it could be a great diagnostic problem for an infectologist. Case report. We report a case of a 39-year old man who was initially clinically suspected to have an infectious central nervous system (CNS) affection, having most similar appearance to neurotuberculosis. Malignancy with bone metastases and lymphoma were also among many possible diagnoses. The patient was later histologically confirmed to have Castleman's disease, analyzing the enlarged inguinal lymph node, which was the key point in rejecting the suspicion of malignancy and tuberculosis. By further analyses, the patient was diagnosed to have mixed connective tissue disorder (MCTD). Vasculitis of mesencephalon and thalamus was detected by magnetic resonance imaging. Conclusion. CD with CNS involvement is very rare as well as CD with MCTD association, making this case even more unique. This case report underlines the importance of definitive histological diagnosis in patients with lymphadenopathia associated with systemic involvement and the need of additional immunological and radiological examinations, as well.
Keywords: castleman disease; diagnostic techniques and procedures; diagnosis, differential; neurologic manifestations; histology